Aplikasi Biochar dan Volume Pemberian Air Terhadap Produksi Benih Kacang Merah Varietas Inerie Ngada di Dataran Rendah Lahan Kering Beriklim Kering - Yosefina Lewar; Mochammad Hasan (Politeknik Negeri Lampung., 2017)
Inerie Ngada variety of red bean plants in East Nusa Tenggara is generally cultivated on a plateau which breadth is very limited, eventhough the lowland in NTT with dry climate and agro-climate conditions is very wide. Due to the limited extent of the existing highlands, the efforts to develop red bean plants in the lowlands need to be done. However, the development of this plant is constrained by the altitude of the place in accordance with the growth of red beans. Differences in the height of the place may affect the climate difference, temperature, humidity and light intensity. Therefore, it is necessary to use technology that can modify the microclimate of plants, one of which is the use of biochar followed by adjusting the volume of watering. Seeds are one of the key successes of farming. The use of quality seeds can increase the production of plants including Inerie Ngada variety of red beans. This study aims to determine the effect of the type of biochar and the volume of water supply on red bean seed production of Inerie variety in lowland with dry climate. The research employed a complete randomized design of biochar factorial factor. The types of biochar were B: B1: rice husk of ranga, B2: wood charcoal, B3: coconut shell charcoal, and B4: sawdust charcoal and water volume (A) factor: A1: 100% of ETc; A2: 85% of ETc; A3: 70% of ETc; A4: 55% of ETc and A5: 40% of ETc. The results of the study showed that there was an interaction between type of biochar and volume of water towards the total of pod content, number of seeds and weight of Ngada Inerie of red beans per plant. The coconut shell charcoal of biochar treatment with 85% Etc of the water supply volume gave the best effect on red bean seeds with total pod content (12,585 pods), number of seeds (32,833 eggs), seed weight (9,493 gr), and seed weight of 100 (31,065 g). Hence, the production of Inerie Ngada of red bean seeds can be developed in dry lowland by using the technology of coconut shell charcoal biochar followed by 85% of Etc of water supply volume.